Y= -x + 2 and y= 3x - 4
As these both equal y, you know that they both equal each other so
-x + 2 = 3x - 4
Third option :)
Answer:
You can Ask nicely about that,
we are not doing your homework for you.
if you have question, put it on the question.
not giving us a doc.
We do not want anything returned
Thankyou
Answer:
x = 2
Step-by-step explanation:
To solve the equation, you need to set both functions equal to each other and simplify to find the value of "x".
f(x) = 2x + 1
g(x) = -x + 7
f(x) = g(x) <----- Given equation
2x + 1 = -x + 7 <----- Insert functions
3x + 1 = 7 <----- Add "x" to both sides
3x = 6 <----- Subtract 1 from both sides
x = 2 <----- Divide both sides by 3
Answer:
see explanation
Step-by-step explanation:
The circumference (C) of a circle is calculated as
C = πd ( d is the diameter )
(4)
Here d = 18, thus
C = 18π in
(5)
Here C = 50π, thus
πd = 50π ( divide both sides by π )
d = 50 in
The radius r is one half of the diameter , thus
r = 50 ÷ 2 = 25 in